Mengembangkan Keterampilan Berpikir Kreatif Pada Anak - Sudirman (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to analyze the process of developing creative thinking skills in children within the context of early childhood education. This issue is important because creativity is one of the 21st-century competencies that supports problem-solving, innovation, and social adaptation abilities, yet in practice, learning is still often oriented towards academic outcomes and uniform activities. The study uses a qualitative approach with a case study design to obtain an in-depth understanding of the dynamics of children's creativity development in the natural context of learning. The research was conducted at an early childhood education institution in Mataram City, West Nusa Tenggara, involving 12 participants consisting of 6 children aged 5–6 years, 3 teachers, and 3 parents selected through purposive sampling techniques. Data collection was carried out through semi-structured interviews, participatory observation, and documentation, meanwhile, the validity of the data was maintained through source triangulation, method triangulation, member checking, and audit trail. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions. The results of the study showed three main themes, namely the importance of free exploration space in learning, the role of teachers as facilitators of creativity through scaffolding and open-ended questions, and family support in providing exploratory stimulation at home. These findings indicate that the development of children's creative thinking skills is influenced by the interaction between the learning environment, pedagogical practices, and family support. This study contributes to strengthening the perspective of social constructivism and divergent thinking in understanding children's creativity, as well as providing practical implications for the development of more exploratory, flexible, and process-oriented learning.